Delinquency theory and prevention: A radical alternative - Carter, Timothy J. (American journal of criminal justice, 1979)
Twentieth century America has seen several delinquency prevention programs come into vogue and then collapse under the pressure of ever increasing rates of delinquency; pressuring policy makers to continue their search for new and better programs. Yet, new prevention programs are not pulled out of a hat. Because these programs are based on certain assumptions about human behavior they are, for the most part, derived from theories of crime and delinquency causation. Pursuing this relationship between theory and practice, this paper grounds the emergence of delinquency prevention with the development of positivist criminology, identifies the conceptual and practical deficiencies of positivist theories of crime and subsequent prevention strategies and presents the prevention directive of contemporary Marxist “Critical Criminology.”